POLITICAL THOUGHT AND MODERNISATION OF THE EAST - S. I. Lunev (Сравнительная политика, 2015)
Abstract: Since the middle of the XX century the Western monopoly on explanation of world development is under erosion. However the atmosphere of intellectual intolerance predominates this process. Despite marginal record of mutual enlightment, theoretical achievements of both West and East have not been subjected to comprehensive dialogue.